Stygomomonia (S.) manchurica, a new species of water mite (Acari: Hydrachnidia: Momoniidae) from the Far East of Russia - Semenchenko, Ksenia A. (Zootaxa, 2008)
Stygomomonia (S.) manchurica sp. n. (Acari: Hydrachnidia: Momoniidae) from the Kedrovaya River, Primory Territory of the Russian Far East is described. The affinity of the new species to its congeners is discussed with emphasis on biogeographical relationships. An annotated checklist of the subgenus Stygomomonia and geographical map of the distribution of Palaearctic species of this subgenus is compiled using published records.